Studi kelayakan LKS berorientasi model inkuiri terbimbing diikuti soal-soal hots pada materi hukum Newton serta usaha dan energi - Pusri Mela; Silvi Yulia Sari; Yenni Darvina; Yurnetti Yurnetti (Universitas Negeri Padang, 2019)
The purposeeof thissstudy was to determineethe level of validity of theworksheet that has been systematically and precisely made. Based on observations at SMAN 8 Padang, the level of concepts mastery and students learning outcomes in Physics were not optimal. The result midterm of physics at SMAN 8 Padang which was generally less than the minimum completeness criteria (KKM). The low student learning outcomes in learning were caused by several factors, firstly the implementation of physics learning has not been carried out by both according to the demands of the 2013 curriculum. According to the teacher, the demands of the 2013 curriculum are too many, including the usingof models, media, and learning assessments. Then Learning resources used in schools are textbooks and students whorsheet, but the students whorksheet( LKS) were not made by teacher. The worksheet used was not were HOTS-oriented yet. While HOTS-oriented questions are very important to train students' high-level thinking skills. After perfecting the product, the validation results obtained an average value of 91.95%. Overall, instructional materials designed are in the valid categories so that they are appropriate for students to use for learning.